Impact of the RaS-RiPP tryglysin and culturing conditions on ex-vivo oral microbiomes - Britta E. Rued; Achal Dhariwal; Brett C. Covington; Mohammad R. Seyedsayamdost; Sophie A. Krivograd; Russell P. Pesavento; Michael J. Federle; Fernanda C. Petersen (npj Biofilms and Microbiomes)
Abstract Natural products are ubiquitously produced by many species that we encounter during our daily lives. One genus, Streptococcus, can produce a wide array of quorum sensing linked natural products known as RaS-RiPPs (ribosomally synthesized and post-translationally modified peptides). Their production is triggered by the induction of an Rgg-SHP quorum sensing system, which senses the presence of SHPs (short hydrophobic peptides) and induces the gene expression of these operons. Previous work has found that streptococcal RaS-RiPPs modulate the growth of different streptococci and might play a role in antibiotic tolerance. This is of particular importance to the oral microbiome, where streptococci are a predominant genus. This study provides the first report on attempts to study the impact of the RaS-RiPP Tryglysin A on ex-vivo oral systems and explores important factors to consider when culturing these systems. We explore how medium selection, atmosphere, growth model, and saliva amount can impact the presence of both bacterial and fungal species. These studies provide the groundwork for determining how RaS-RiPP producing Streptococci might impact the composition and function of oral microbiome communities, as well as important aspects to consider when culturing ex-vivo oral systems.